2010
DOI: 10.1128/jvi.02651-09
|View full text |Cite
|
Sign up to set email alerts
|

Virological Synapse-Mediated Spread of Human Immunodeficiency Virus Type 1 between T Cells Is Sensitive to Entry Inhibition

Abstract: Human immunodeficiency virus type 1 (HIV-1) can disseminate between CD4؉ T cells via diffusion-limited cell-free viral spread or by directed cell-cell transfer using virally induced structures termed virological synapses. Although T-cell virological synapses have been well characterized, it is unclear whether this mode of viral spread is susceptible to inhibition by neutralizing antibodies and entry inhibitors. We show here that both cell-cell and cell-free viral spread are equivalently sensitive to entry inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
284
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(316 citation statements)
references
References 46 publications
28
284
4
Order By: Relevance
“…In the absence of CD4 availability on the T cell or when gp120 on the viral surface is prevented from binding CD4, the viruses remain associated with the dendritic cell, perhaps via interactions with dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) (35,36) (other receptors are possible) until the formation of productive synapses with T cells that are capable of supporting gp120-CD4 interaction. We note that virological synapses between T cells alone have also been described (7,32,37), and the available data suggest that these synapses may be less complex and devoid of the large membrane encasement reported here with mature dendritic cells.…”
Section: Discussionmentioning
confidence: 93%
“…In the absence of CD4 availability on the T cell or when gp120 on the viral surface is prevented from binding CD4, the viruses remain associated with the dendritic cell, perhaps via interactions with dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) (35,36) (other receptors are possible) until the formation of productive synapses with T cells that are capable of supporting gp120-CD4 interaction. We note that virological synapses between T cells alone have also been described (7,32,37), and the available data suggest that these synapses may be less complex and devoid of the large membrane encasement reported here with mature dendritic cells.…”
Section: Discussionmentioning
confidence: 93%
“…The predominant mode of cell-cell spread of HIV-1 is across virusinduced immune cell contacts termed virological synapses [5] that constitute >90% of cell-cell transmission events in vitro [6], although longer range cell-cell transmission via filopodia [7] and membrane nanotubes have also been reported [8]. Notably, cell-cell spread of HIV-1 is significantly more efficient than equivalent cell-free infection [9][10][11][12][13][14], with the increased infection kinetics of cell-cell spread attributed to a combination of factors including polarised budding of the virus towards the target cell, receptor clustering on the target cell enriching for viral entry receptors, and the close physical contact between cells limiting the requirement for prolonged virus diffusion [5,10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that virological synapses are dynamic contacts with a mean contact time of 62 min and that antibody targeting Env-CD4 binding can prevent HIV-1 infection when added up to 3 h after mixing infected and uninfected cells [10]. To determine whether J3 can also neutralise cell-cell spread after synapse formation, we added the antibody at the time of mixing infected and uninfected cells (t = 0 h) or 1 h and 3 h post-mixing.…”
Section: J3 Inhibits Virological Synapse Formationmentioning
confidence: 99%
See 2 more Smart Citations